2010
DOI: 10.1007/s00011-010-0300-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine reduces neuronal cell apoptosis by inhibiting Toll-like receptor 4/nuclear factor kappa-B-dependent inflammatory responses in traumatic rat brain injury

Abstract: OMT may inhibit TLR4/NF-κB-dependent inflammatory responses, and furthermore lessen neuronal cell apoptosis after TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 20 publications
3
31
0
1
Order By: Relevance
“…For example, Zhang et al (11) have demonstrated that OM effectively reduces the serum TNF-α level in rats with L-arginine-induced acute pancreatitis. It has also been shown that OM is able to reduce neuronal cell apoptosis by inhibiting Toll-like receptor 4/nuclear factor κ-B-dependent inflammatory responses in traumatic rat brain injury (14). Collectively, we concluded that OM may protect mice against BLM-induced PF by decreasing the production or activities of these pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…For example, Zhang et al (11) have demonstrated that OM effectively reduces the serum TNF-α level in rats with L-arginine-induced acute pancreatitis. It has also been shown that OM is able to reduce neuronal cell apoptosis by inhibiting Toll-like receptor 4/nuclear factor κ-B-dependent inflammatory responses in traumatic rat brain injury (14). Collectively, we concluded that OM may protect mice against BLM-induced PF by decreasing the production or activities of these pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 51%
“…(Kushen) that has been approved by the State Food and Drug Administration of China for treating hepatitis B (7,8). Cumulative evidence has suggested that OM possesses multiple biological and pharmacological properties, such as anti-inflammatory (9)(10)(11), antitumor (12,13), anti-apoptotic (14), antifibrotic (15), antioxidant (16), and antiarrhythmic activities (17). Chen et al (18) demonstrated that…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we consistently found that TNF-α plasma level was elevated following AP induction. Various published data have demonstrated that oxymatrine suppresses TNF-α in rats with traumatic brain injury, dextran sulfate sodium-induced colitis, and intestinal I/R injury [19,22,33]. In addition, oxymatrine has been reported to inhibit the quartz-induced secretion of TNF-α by pulmonary alveolar macrophages, thereby antagonizing the damage effect of quartz on the membrane of alveolar macrophages [34].…”
Section: Discussionmentioning
confidence: 99%
“…It has been used to treat chronic hepatitis B patients in China for decades with confirmed safety [14]. Recent evidence has shown that oxymatrine possesses a wide variety of pharmacological effects, including anti-inflammatory, anti-apoptosis, anti-tumor, anti-hepatic fibrosis, and anti-arrhythmic functions [15][16][17][18][19]. In addition, oxymatrine has also been reported to exert a protective effect against end-organ (liver, heart, intestine, and brain) ischemia or ischemia/reperfusion injury [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Oxymatrine significantly ameliorates L-arginine-induced acute pancreatitis by the reduction of plasma amylase, D-lactic acid, tumor necrosis factor alpha concentration, serum diamine oxidase, lipase activity, and pancreatic myeloperoxidase activity. 7 The administration of oxymatrine can significantly inhibit inflammatory responses.…”
Section: Anti-inflammatory Propertiesmentioning
confidence: 99%